Determinants of female sexual orgasms. (1st January 2016) - Kontula, Osmo; Miettinen, Anneli
Abstract : Background: The pursuit of sexual pleasure is a key motivating factor in sexual activity. Many things can stand in the way of sexual orgasms and enjoyment, particularly among women. These are essential issues of sexual well-being and gender equality. Objective: This study presents long-term trends and determinants of female orgasms in Finland. The aim is to analyze the roles of factors such as the personal importance of orgasms, sexual desire, masturbation, clitoral and vaginal stimulation, sexual self-esteem, communication with partner, and partner's sexual techniques. Design: In Finland, five national sex surveys that are based on random samples from the central population register have been conducted. They are representative of the total population within the age range of 18–54 years in 1971 ( N =2, 152), 18–74 years in 1992 ( N =2, 250), 18–81 years in 1999 ( N =1, 496), 18–74 years in 2007 ( N =2, 590), and 18–79 years in 2015 ( N =2, 150). Another dataset of 2, 049 women in the age group of 18–70 years was collected in 2015 via a national Internet panel. Results: Contrary to expectations, women did not have orgasms that are more frequent by increasing their experience and practice of masturbation, or by experimenting with different partners in their lifetime. The keys to their more frequent orgasms lay in mental and relationship factors. These factors and capacities included orgasm importance, sexual desire, sexual self-esteem, and openness of sexual communication with partners. Women valued their partner's orgasm more than their own. In addition, positive determinants were the ability to concentrate, mutual sexual initiations, and partner's good sexual techniques. A relationship that felt good and worked well emotionally, and where sex was approached openly and appreciatively, promoted orgasms. Conclusion: The findings indicate that women differ greatly from one another in terms of their tendency and capacity to experience orgasms. The improvements in gender equality and sexual education since the 1970s have not helped women to become more orgasmic. Neither has the major increase in masturbation habits (among women in general). One challenge for future studies is to understand why women value their partner's orgasms more than their own.